PERENCANAAN SISTEM PLAMBING DAN HIDRAN KEBAKARAN PADA PROYEK PEMBANGUNAN HOTEL PESONA ALAM - Ivana Patricia Lilipaly; Ririn Endah Badriani; Yeny Dhokhikah (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
Pesona Alam Hotel is one of the hotels located in the Cisarua area, Bogor. An adequate plumbing system and fire hydrant system planning are needed to support the Comfort and safety of hotel visitor activities. The Plumbing Tool Load Unit Method is used in determining the dimensions of both clean and wastewater. Isometric depiction of piping networks and determining the diameter of clean water pipes is assisted by Pipe Flow Expert software. Based on the calculation, it is found that the need for clean water per day at Pesona Alam Hotel is 230 m3/day with the required diameter of clean water pipes of 0.5